Reference-free SNP discovery for the Eurasian beaver from restriction site-associated DNA paired-end data - Senn, H; Ogden, R; Cezard, T; Gharbi, K; Iqbal, Z; Johnson, E; Kamps-Hughes, N; Rosell, F; McEwing, R (2013)
In this study, we used restriction site-associated DNA (RAD) sequencing to discover SNP markers suitable for population genetic and parentage analysis with the aim of using them for monitoring the reintroduction of the Eurasian beaver (Castor fibre) to Scotland. In the absence of a reference genome for beaver, we built contigs and discovered SNPs within them using paired-end RAD data, so as to have sufficient flanking region around the SNPs to conduct marker design. To do this, we used a simple pipeline which catalogued the Read 1 data in stacks and then used the assembler cortex-var to conduct de novo assembly and genotyping of multiple samples using the Read 2 data. The analysis of around 1.1 billion short reads of sequence data was reduced to a set of 2579 high-quality candidate SNP markers that were polymorphic in Norwegian and Bavarian beaver. Both laboratory validation of a subset of eight of the SNPs (1.3% error) and internal validation by confirming patterns of Mendelian inheritance in a family group (0.9% error) confirmed the success of this approach. © 2013 John Wiley and Sons Ltd.